ANALYZING THE INFLUENCE OF CUSTOMER EXPERIENCE OF CALL CENTRE TOWARDS BRAND LOYALTY OF TELKOMSEL USERS IN MANADO - Item, Alwins Januard (Universitas Sam Ratulangi, 2013)
A fairly rapid growth in Indonesian telecommunications industry has encourages the competition among existing providers. The need to increase customer satisfaction through CRM for every company is now considered to be more important. Nowadays, call centre not only limited to provide convenience feeling to the customers in keep in touch with the company. The extended function of this service can be use to build loyalty to a brand. Telkomsel as one of the famous provider also provide call centre in order to reach their customer all over Indonesia area and create the brand loyalty of the customer. This research is to analyze the experience of the customer when dealing with call centre in creating brand loyalty at PT Telkomsel. This research is conducted by using qualitative research and case study method with 9 respondents who are the customer of Telkomsel in Manado area as sample of respondents. The result shows that staff attitude has no direct influence on brand loyalty. On the other hand, the empathy and perception of commitment to service quality and customer satisfaction have direct influence on brand loyalty. Keywords: customer experience, brand Loyalty